Microbial nutrient limitation and carbon use efficiency in saline-alkali soil amended with biochar: insights from ecoenzymatic C:N:P stoichiometry - Guorui Zhang; Lan Zhang; Ziyue Shi; Yunfeng Yang; Jie Liu (Biochar)
Abstract Biochar application is known to improve soil quality, enhance nutrient bioavailability, and increase carbon retention. However, its effects on ecoenzymatic activities and stoichiometric relationships in saline-alkali soils remain poorly understood. This study examines how biochar amendments influence microbial stoichiometry, nutrient limitations, and carbon use efficiency in saline-alkali soils. We compared two types of biochar—acid-modified biochar (pH 2.3) and alkaline biochar (pH 8.8)—at application rates of 1%, 2%, and 5% in soils planted with Medicago sativa L. Our results demonstrated that alkaline biochar increased enzymatic C:N stoichiometry at higher rates, while acid-modified biochar decreased it at lower rates. Both biochar types reduced enzymatic C:P and N:P stoichiometry; alkaline biochar shifted microbial metabolism from nitrogen to phosphorus limitation, while acid-modified biochar alleviated nitrogen limitation at rates of 2% and 5%. Furthermore, alkaline biochar at rates of 2% and 5% reduced microbial carbon limitation and enhanced carbon use efficiency, whereas acid-modified biochar did not. Microbial carbon use efficiency was consistently higher with alkaline biochar than with acid-modified biochar at equivalent application rates. These findings highlight that the impact of biochar on soil microbial processes depends on the biochar feedstock type, with differences in surface adsorption properties, nutrient supply, pH, and liming effects driving changes in soil properties, microbial community dynamics, and plant growth. Our study offers insights into optimizing nutrient cycling and carbon sequestration in saline-alkali soils, demonstrating the potential of biochar in sustainable soil management. Graphical Abstract